Factors associated with condom use and HIV testing among young men who have sex with men: a cross-sectional survey in a random online sample in Sweden. (17th May 2018) - Johansson, Klara; Persson, Kristina Ingemarsdotter; Deogan, Charlotte; El-Khatib, Ziad
Abstract : Objectives: The objectives are to analyse social determinants of sexual health behaviour (condom use and HIV testing) among young, internet-active, cis men who have sex with men (MSM) in a high-income country. The aspects of sexual health behaviour analysed here are condomless anal intercourse with one or more new or casual partner(s), condomless anal intercourse during the most recent sex with a man and HIV testing. Methods: A randomised sample of men active on Sweden's main online community for Lesbian, Gay, Bisexual and Trans people responded to an online survey (response rate 19%). A subsample of young people, aged 15–29, was analysed (effective sample 597–669) using multivariable logistic regression with respect to factors associated with condomless anal intercourse with one or more new or casual partner(s), condomless anal intercourse at most recent sex and not having had a test for HIV. Results: Low education, being single and living in a metropolitan area were found to be independently associated with condomless anal intercourse with new or casual partner(s). Sex with a steady partner was associated with condomless anal intercourse during the most recent sex. Knowledge of where to get tested, high education, being born outside Sweden and condomless anal intercourse with new or casual sex partner(s) were independently associated with having been tested for HIV. Conclusions: The factors associated with sexual health behaviour among young MSM are complex, and preventive messages need to be tailored accordingly.